Screening and Detection of Pancreatic Cancer - Gonda, Tamas A; Lucas, Aimee; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Screening and early detection of pancreatic cancer has the potential to substantially impact outcomes in this deadly disease. Over the last ten years several cohort studies have been conducted and report on the yield of screening in high risk populations. With better understanding of the cellular compartments and the genetic and epigenetic changes that occur, biomarkers have also emerged as promising means of early detection. In this paper we summarize the results of the latest screening cohort and highlight a novel proteomic approach that may be used in future biomarker studies. Image: Factors responsible for the activation of pancreatic stellate cells.